Communication power - Castells, Manuel. 1942- (New York : Oxford University Press, 2009)
"In this book, Manuel Castells analyses the transformation of the global media industry by this revolution in communication technologies. He argues that a new communication system, mass self-communication, has emerged, and power relationships have been profoundly modified by the emergence of this new communication environment. Created in the commons of the Internet this communication can be locally based, but globally connected. It is built through messaging, social networking sites, and blogging, and is now being used by the millions around the world who have access to the Internet."--BOOK JACKET.
1. Power in the Network Society -- 2. Communication in the Digital Age -- 3. Networks of Mind and Power -- 4. Programming Communication Networks: Media Politics, Scandal Politics, and the Crisis of Democracy -- 5. Reprogramming Communication Networks: Social Movements, Insurgent Politics, and the New Public Space -- Conclusion: Toward a Communication Theory of Power.
Includes bibliographical references (p. 489-542).
Keywords: Mass media -- Social aspects; Communication -- Social aspects; Globalization